The interplay between career decision making efficacy, career exposure and career choice of undergraduates: does gender matters - Abd. Karim, Nor Izan; Mohd Rasdi, Roziah (Human Resource Management Academic Research Society, 2021)
Lack of career exposure and rightful decision-making among university students has led to failure and inability to make a satisfying career choice. This lack of exposure emanates as a result poor supervision of programs which includes career education initiatives, workshops, seminars and internship programs which develops career self-efficacy among both of the genders. The aim of this study was to examine whether gender moderated the relationship between career decision-making self-efficacy, career exposure and career choice of Malaysian undergraduates. This study has employed a cross-sectional survey which involves a sample of 131 final-year students from eight faculties in a selected Malaysian public research university. The outcome of this study has demonstrated that there was a positive and moderate relationship between career decision-making self-efficacy and career choice (r=0.452; p<0.001). The findings further indicate a positive and strong relationship between career exposure and career choice (r=0.745; p<0.001). But gender did not moderate the relationship between career decision-making self-efficacy and career choice; neither did it moderate the relationship between career exposure and career choice. The implications of this study are that, both the colleges and faculties should offer a helping hand in encouraging student participation in activities such as organizing competition and designing programs that suit students’ needs and challenges. It is recommended for universities in Malaysia to initiate a career counseling unit in all the universities and regenerate the existing ones, as that will facilitate lingering issues relating to career choice, career exposure and career decision making efficacy.